2021
DOI: 10.1111/ans.16674
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and surgical outcomes in laparoscopic liver resections: a systematic review

Abstract: Background Laparoscopic liver resection is gaining momentum; however, there is limited evidence on its efficacy and safety in obese patients. The aim of this study was to examine the relationship between BMI and outcomes after laparoscopic liver resection (LLR) using a systematic review of the existing literature. Methods A systematic search of Medline (Ovid 1946–present), PubMed (NCBI), Embase (Ovid 1966–present) and Cochrane Library was conducted using the Preferred Reporting Items for Systematic Reviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…However, a recent systematic review that investigated the relationship between BMI and outcomes following laparoscopic liver resection found that the estimated blood loss rates were similar between obese and nonobese patients. 14 Although this outcome was not different, laparoscopic surgery is often more difficult in obese patients even if it can be completed safely. This factor might deserve further study.…”
Section: Discussionmentioning
confidence: 94%
“…However, a recent systematic review that investigated the relationship between BMI and outcomes following laparoscopic liver resection found that the estimated blood loss rates were similar between obese and nonobese patients. 14 Although this outcome was not different, laparoscopic surgery is often more difficult in obese patients even if it can be completed safely. This factor might deserve further study.…”
Section: Discussionmentioning
confidence: 94%
“…Liver parenchyma dissection and hepatic hilum treatment are sometimes challenging despite a large skin incision and gastrointestinal tract and greater momentum compression in OLR [116][117][118]. In contrast, pneumoperitoneum, head-up position, and high magnification-even at deep portions in the caudal view-can provide sufficient free space to control the forceps in LLR, even in patients who are overweight and obese (Caudal approach, Figure 3) [119][120][121]. There is some disagreement as to whether obesity increases the risk of conversion [12,111,113,122,123], but the LLR is reported to decrease intraoperative blood loss and postoperative complications compared with OLR even in obesity [113,118,121,124].…”
Section: Obesitymentioning
confidence: 99%
“…In contrast, pneumoperitoneum, head-up position, and high magnification-even at deep portions in the caudal view-can provide sufficient free space to control the forceps in LLR, even in patients who are overweight and obese (Caudal approach, Figure 3) [119][120][121]. There is some disagreement as to whether obesity increases the risk of conversion [12,111,113,122,123], but the LLR is reported to decrease intraoperative blood loss and postoperative complications compared with OLR even in obesity [113,118,121,124]. Moreover, obesity did not affect conversion rate, operation time, or blood loss in the LLR compared with non-obesity [113,122,123].…”
Section: Obesitymentioning
confidence: 99%
“…The impact of BMI on the outcomes of LR has been well‐reported with contrasting results from different studies 3 . In our opinion and experience, the effect of increasing BMI on the difficulty of LR is related to the increased likelihood of hepatic steatosis and hence increasing mass/volume of the liver and transection surface 4 .…”
mentioning
confidence: 91%